A case of pioneering subcutaneous implantable cardioverter defibrillator intervention in Timothy syndrome - Zixi Zhang; Keke Wu; Zhihong Wu; Yunbin Xiao; Yefeng Wang; Qiuzhen Lin; Cancan Wang; Qingyi Zhu; Yichao Xiao; Qiming Liu (BMC, 2024)
Abstract This case report presents a notable instance of subcutaneous implantable cardioverter defibrillator (S-ICD) implantation in a 9-year-old patient diagnosed with Timothy syndrome (TS), which is a rare condition characterized by mutations in the CACNA1c gene. Conventional therapies often have limited efficacy in managing TS. This case is significant, as it represents the youngest age for S-ICD implantation recorded in mainland China. While the absence of ventricular arrhythmias during hospitalization and follow-up is encouraging, it is not sufficient to conclusively establish the safety and feasibility of this intervention in young TS patients. Further research is needed to evaluate the long-term outcomes and to consider S-ICD as a potential standard treatment option for TS. Additionally, there is a need for a more detailed exploration of the molecular mechanisms underlying gene therapy and personalized interventions.